Immediate generation and audiovisual communication (Research, Society and Development, 2018)
In this research we will perform a mapping of the consumption form of Generation Z, we will understand the reason for being called immediatists and how they behave through society and technology. We will analyze the data collected and understand how convergence integrates the young members of Generation Z into the consumption of audiovisual content, we will see how the flow of these receivers works through the main means of distribution of the audiovisual in Brazil, with the intention of understand how the Internet and the digitization of audiovisual content may influence the distribution and consumption of the final product. The research seeks to identify how Generation Z searches for new content on the available display platforms and how they are transforming the audiovisual production chain and presenting challenges and opportunities to the market, that needs to deal with new forms of consumption, new business models and new demands of an increasingly demanding consumer generation, immediatist, accustomed to multiplatform access and content on demand. In this project we will understand how the Generation Z called Immediatist consumes audiovisual products.